The Relationship between Health Locus of Control and Iranian Women's Beliefs toward Pap Smear Screening - Marzieh Saei Ghare Naz; Tayebeh Darooneh; Farzaneh Rashidi Fakari; Farhnaz Kholosi Badr; Fahimeh Hajizadeh; Giti Ozgoli (Shiraz University of Medical Sciences, 2019)
Background: Cervical cancer has a high prevalence and mortality, while early diagnosis greatly reduces its complications. Therefore, it is important to identify the factors affecting the screening of cervical cancer. Studies have shown that health locus of control plays an important role in beliefs about screening. This study aimed to identify the correlation between health locus of control and beliefs about Pap smear among women. Methods: This was a descriptive study which was conducted cross-sectionally. It was conducted on 250 married women who had the inclusion criteria and attended health centers selected by Shahid Beheshti University of Medical Sciences in Oct. 2017 to February 2018 (a period of 5 months). Data collection tools included a demographic information questionnaire, multidimensional health locus of control scale, and the Pap Smear Belief Questionnaire (PSBQ). Data analysis was carried out through SPSS (v.17) using statistical tests including correlation and regression. The significance level was considered 0.05. Results: Among the participants, 50.8% never had a history of undergoing a Pap smear test. The mean scores for the internal health locus of control (IHLC), chance health locus of control (CHLC), and powerful others health locus of control (PHLC) were 22.59±5.32, 22.84±4.65 , and 24.54±4.28, respectively. The total score for the Pap smear belief had a significant positive correlation with two dimensions: IHLC (r=0.209, P=0.001) and PHLC (r=0.216, P=0.001). In addition, based on the results of the linear regression analysis, the scores of IHLC (R2=0.03, P=0.004), PHLC (R2=0.036, P=0.003), and CHLC (R2=0.16, P=0.04) were the predictors of the total score for the Pap smear belief. Conclusion: Our results showed that all dimensions of the health locus of control were the predictors of belief in women's Pap smear screening. It is necessary that health care providers hold programs for health locus control of cervix cancer prevention in Iranian women.